UNDERSTANDING INDIA’S RISE: A STUDY OF DOMINANT STRATEGIC IDEAS - Dasgupta, Anwesha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India’s enhanced power projection capabilities, expanded economic ties, multifaceted global engagements have ushered it as a rising power with potential for a substantial global status. However, as an emerging power India’s ascribed objectives and ideas which it strives to seek in the world order is marred in obscurity. Such ambivalence has led to assumptions and criticisms concerning India’s lack of vision or a strategic worldview as a rising power. This article tries to explain India’s strategic worldview through five dominant interests which have been constantly reflected in India’s association and deliberations with international order. The aim is to provide a simplified, coherent representation of the dominant ideas emergent India endeavours in the present international system.